NILAI-NILAI PENDIDIKAN AKHLAK DALAM KITAB BERJANZI - Sunani, Eneng (STAI Darul Qalam Tangerang, 2024)
Literary works always provide a message or mandate to do good, and the community or readers are invited to uphold moral norms. In different ways literature, philosophy and religion, are considered as a means to cultivate a subtle, human and cultured human soul. (Djojonegoro, 1998:425). The writing of this thesis uses a type of library research. Therefore, in order to obtain the required data, the researcher studied literature books relevant to the title of this thesis. Literary research with language objects is focused on the use of language as a means of communication; literary research with content objects focused on the value, benefits or usefulness of literary works in human life; Meanwhile, literary research with aesthetic objects is directed to the study of the existence of literary works as works of art that contain life values. In this regard, moral research was carried out in the Book of Al-Barzanji with the formulation of the problem (1) how to describe individual/personal moral values in the form of commands in the book of Al-Barzanji, (2) how to describe social moral values in the form of commands in the book of Al-Barzanji. (3) What is the value of education in the book of Berzanji. This research was conducted with the aim of obtaining a description of the representation of values in the Book of Al-Barzanji in the form of (1) obtaining a description of individual/personal and social moral values in the book of Al-Barzanji, (2) obtaining a description of educational values in the book of Al-Barzanji